Synthesis of poly(lactic acid): A review - Mehta R.; Kumar V.; Bhunia H.; Upadhyay S.N. (My University, 2025)
Poly(lactic acid), a biodegradable polymer, has been studied extensively during the past 15 years. This paper presents a review on poly(lactic acid) (PLA) with focus on its stereochemistry, synthesis via ringopening polymerization, reaction kinetics and thermodynamics, synthesis of low molecular weight polymer, a continuous process for production of PLA from lactic acid, and blends. The different polymerization mechanisms, which have been proposed in the literature, are also summarized. Various catalyst systems, solvents, and reaction temperature and time give products of an entire range of molecular weights, ranging from a few thousand to over a million. Modeling and simulation of the ringopening polymerization of PLA is also discussed.